2017
DOI: 10.1590/0103-6440201601558
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Zoledronic Acid in Experimental Periapical Lesions in Rats: An Imaging and Histological Analysis

Abstract: The aim of this study was to assess the imaging and histological features of experimental periapical lesions, including the adjacent alveolar bone, in rats under zoledronic acid treatment. The study used 40 male Wistar rats distributed into 8 groups of 5 animals each: G1: induction of periapical lesion (PL) and weekly intraperitoneal administration (WIPA) of saline solution (0.9% NaCl) for 4 weeks; G2: PL induction and WIPA of zoledronic acid (0.15 mg/kg/week) for 4 weeks; G3: PL induction and WIPA of saline s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…The results of this study are in accordance with previous studies performed by Wayama et al [48] and Rao et al [49], which induced apical periodontitis in hypoestrogenic rats and in ovariectomized rats (respectively) treated with zoledronic acid, resulting in a decrease in periapical lesion progression [48,49]. Similarly, França et al [50] showed that rats treated with zoledronic acid had smaller periapical lesions when compared to the control group [50].…”
Section: Discussionsupporting
confidence: 92%
“…The results of this study are in accordance with previous studies performed by Wayama et al [48] and Rao et al [49], which induced apical periodontitis in hypoestrogenic rats and in ovariectomized rats (respectively) treated with zoledronic acid, resulting in a decrease in periapical lesion progression [48,49]. Similarly, França et al [50] showed that rats treated with zoledronic acid had smaller periapical lesions when compared to the control group [50].…”
Section: Discussionsupporting
confidence: 92%
“…Animals treated with alendronate had rare signs of alveolar bone resorption after 14 days of periodontitis induction, in addition to greater bacterial contamination and presence of osteonecrosis with bone exposure at 21 days of ligature use. Likewise, other authors found less resorption in the periapical bone region of the animals that received high doses of ZOL for 8 weeks, by means of imaging and histological analyses [ 4 21 ].…”
Section: Discussionmentioning
confidence: 91%
“…In fact, it was shown that intravenous administration of bisphosphonates increases the risk of developing jaw osteonecrosis, and that the number of registered patients with bisphosphonate related jaw osteonecrosis rose with the increase of the time of intravenous therapy (58). In addition, previously reported research showed that local application of bisphosphonates for a short time period did not result in any side effects, but rather have had a beneficial effect on the healing processes in alveolar bone (31,32,34,(42)(43)(44).…”
Section: Jaw Osteonecrosis As a Side Effect Of Bisphosphonate Therapymentioning
confidence: 95%
“…Similarly to Alendronate, the treatment with Zolendronate also resulted in the reduction of lesions' dimensions, but it did not show any change in the intensity of inflammatory infiltrate. A study of Franca et al (34) showed that Zolendronate was significantly more efficient in alternating the development of periapical lesions when used prior to their induction then after. In has been shown that Zolendronate compensated for the estrogen deficiency in animal models of postmenopausal osteoporosis, inducing ostoeclast apoptosis and inhibiting their differentiation, thus reducing the number of Tartrate resistant acid phosphatase (TRAP) positive cells and bone resorption (35).…”
Section: Periapical Lesions and Bisphosphonatesmentioning
confidence: 99%